Is Time’s Asymmetry Related to Irreversible Processes and the Second Law? - Arieh Ben-Naim (Entropy, 2023)
In this article, we start by describing one of the most characteristic properties of time: “time can never decrease”. From this property, numerous authors have concluded that irreversible processes, that always proceed in one direction, must be related to time’s arrow. It is shown that while time’s decrease can never occur, irreversible processes can be reversed, although with extremely low probability. Similarly, it is argued that both entropy and the Second Law are timeless, i.e., have nothing to do with either time or with time’s arrow.